Isolation of euryhaline microalgal strains from tropical waters of Brunei Darussalam for potential biomass production - WARDINA ROSELI; YASUAKI TANAKA; HUSSEIN TAHA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Roseli W, Tanaka Y, Taha H. 2023. Isolation of euryhaline microalgal strains from tropical waters of Brunei Darussalam for potential biomass production. Biodiversitas 24: 4651-4660. Rapid urbanization has increased the accumulation of excess nitrogen (N) and phosphorus (P) in natural water bodies (eutrophication). Microalgae are seen as a viable candidate to resolve the problem due to their ability to absorb nutrients from the eutrophicated water (phycoremediation). Euryhaline microalgae could significantly benefit because they can tolerate various salinities while maintaining high biomass productivity. This study aimed to isolate euryhaline microalgae from tropical waters and evaluate the algae's potential to produce biomass and absorb nutrients in a wide range of salinities. Three strains labeled W1, W2, and W3 were isolated from Brunei waters and confirmed by DNA barcoding as Desmodesmus sp., Micractinium sp., and Chlorococcum sp., respectively. These strains were screened for salinity tolerance by exposing them to eight conditions (salinity 0, 5, 10, 15, 20, 25, 30, and 35) and evaluated for their high growth performance based on optical density. While the growth of Desmodesmus sp. and Chlorococcum sp. decreased from its highest value by 51% and 45%, respectively, the growth of Micractinium sp. was only reduced by 30%, and therefore, Micractinium sp. was considered to be the most euryhaline species and studied further in the next scale-up experiment. Micractinium sp. was cultivated at salinities of 0, 15, and 30 and recorded the highest biomass production of 54.1 ± 6.0 mg L?1 d?1 at salinity 15. Furthermore, they produced high amounts of N and P in their biomass, indicating that they are suitable for the phycoremediation of eutrophic water bodies. Therefore, Micractinium sp. is a potential candidate for open-pond cultivation because of its tolerance to a wide range of salinities and high biomass productivity.